About proportionality in the application of preventive prison measures - Goicochea Elías, José Julio (2019)
It is mandatory that the Prosecutors justify because they ask for penalties. It would be ideal for them to carry out a development of argumentation similar to the instrument they apply, indicating the reasons that make their request permissive. Nothing exempts them from dispensing with an effort of justification when they intend to deprive a human being of their freedom. A Iushumanist policy hopes that the doors of justice are always open so that form of state intervention produces the same effect with a lower social cost. As Master PieroCalamandrei said the Judge before applying Law, must first apply justice.